A cryogenic CMOS chip for generating control signals for multiple qubits - Pauka, S. J.; Das, K.; Kalra, R.; Moini, A.; Yang, Y.; Trainer, M.; Bousquet, A.; Cantaloube, C.; Dick, N.; Gardner, Geoff; Manfra, M. J.; Reilly, David (Nature Electronics, 2021)
Scaled-up quantum computers will require control interfaces capable of the manipulation and readout of large numbers of qubits, which usually operate at millikelvin temperatures. Advanced complementary metal–oxide–semiconductor (CMOS) technology is an attractive platform for delivering such interfaces. However, this approach is generally discounted due to its high power dissipation, which can lead to the heating of fragile qubits. Here we report a CMOS-based platform that can provide multiple electrical signals for the control of qubits at 100 mK. We demonstrate a chip that is configured by digital input signals at room temperature and uses on-chip circuit cells that are based on switched capacitors to generate static and dynamic voltages for the parallel control of qubits. We use our CMOS chip to bias a quantum dot device and to switch the conductance of a quantum dot via voltage pulses generated on the chip. Based on measurements from six cells, we determine the average power dissipation for generating control pulses of 100 mV to be 18 nW per cell. We estimate that a scaled-up system containing a thousand cells could be cooled by a commercially available dilution refrigerator.